Identification and Quantification of Volatile and Phenolic Compounds Composition in Buckwheat Sprouts by GC/MS and HPLC - Kim, Sun-Ju; Musfiqur Rahman, Md.; Lee, Min-Kee; Min Seo, Jeong; Valan Arasu, Mariadhas; Suzuki, Tatsuro; Al-Dhabi, N.A.; Yoon, Young-Ho; Shim, Jae-Han (Asian Journal of Chemistry, 2014)
The objective of this study was to determine the contents of volatile and phenolic compounds from 10 varieties of buckwheat sprouts. GC/MS analysis guided to identify amines and their derivatives (5), alcohol and derivatives (7), aldehydes (3), acids (4), ketone and derivatives (5), ester and derivatives (7). Alcohols and ester derivatives shared highest contents among all of the volatile compounds determined (20 %). Phenolic compounds, including chlorogenic acid, four C-glycosylflavones (orientin, isoorientin vitexin, isovitexin), rutin and quercetin, were determined in the seed sprouts. The contents of total phenolic compounds ranged from 32.86 to 50.0 mg/g dry weight. Based on these results, the presence of different groups of volatile and phenolic compounds in all the varieties of buckwheat vegetables conformed that it can be regarded as a potent source of functional food.